Measurement of Wγ and Zγ production in proton-proton collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
We present studies of W and Z bosons with associated high energy photons produced in pp collisions at √ s = 7 TeV. The analysis uses 35 pb−1 of data collected by the ATLAS experiment in 2010. The event selection requires W and Z bosons decaying into high pT leptons (electrons or muons) and a photon with ET > 15 GeV separated from the lepton(s) by a distance ∆R(l, γ) > 0.7 in η-φ space. A total of 95 (97) pp → e± νγ + X (pp → µ± νγ + X) and 25 (23) pp → e+ e− γ + X (pp → µ+ µ− γ + X) event candidates are selected. The kinematic distributions of the leptons and photons and the production cross sections are measured. The data are found to agree with Standard Model predictions that include next-to-leading-order O(ααs ) contributions.